تجليات احتجاب المرأة وسفورها في الشعر العربي قبل الإسلام: دراسة سيميائية = Manifestations of woman’s veiling and unveiling of the face in pre-Islamic Arabic poetry: a semiotic study - Yaacob, Adli; M.Melhi, Amal Qasem (2021)
The present study concerns the notion of woman’s veiling and unveiling of the face in Pre-Islamic Arab community, identifying, as an objective, the most important semiotic manifestations in the poetry of that period. Contrary to woman after the advent of Islam, in the Pre-Islamic period, woman was not controlled by religious values, but rather by tribal customs and conventions based on social caste (free or slave). The study will draw on the interpretative semiotic approach of Borres which follows the social model of semiosis a community has produced. To obtain scientific results, we referred to Pre-Islamic Arabic poetry, for this genre is considered the most important reference for Arabs in and after the Pre-Islamic era. The study is based on two axes: the first concerns the manifestations of woman’s veiling of the face and body in Pre-Islamic poetry; the second deals with the issue of woman’s unveiling of the face and body as manifested in the poetry of the same period. As findings, the study shows that woman’s veiling of the face is a deep-rooted tradition in the Pre- Islamic Arab community, partially connected with freedom. To put it differently, while the veil, in various forms and shapes, connected with free women other than slave-girls, free women’s unveiling of the face happened occasionally and under special circumstances and rituals.